The role of patient volunteers in Fangcang Shelter Hospital during the Omicron wave of COVID-19 pandemic in Shanghai, China: a qualitative study - Zhu, Lingyan; Xu, Mengqi; Ruan, Tiantian; Huang, Xiaoli; Cen, Jue (Frontiers in Public Health, 2023)
Objective: During the Omicron wave of the COVID-19 pandemic in Shanghai, Fangcang Shelter Hospital (FSH) served as the major way in patient quarantine. Many COVID patients served as volunteers in FSH providing a lot of assistance for the medical workers and other Covid patients. The aim of this study was to explore the experience of patient volunteers working in the FSH. Methods: This is a qualitative study using semi-structured interviews. Thirteen patient volunteers working in an FSH in Shanghai were included. Thematic analysis was applied to data analysis. Results: Four themes and nine subthemes were identified. The wishes to give back to society and the responsibility of politics and religion were the main reasons for the patients to serve as volunteers in FSH. The patient volunteers served as the bridge to reduce the communication barriers between other patients and healthcare professionals. They also provided support in supply distribution and psychological counseling. They viewed voluntary work as a usual task and tried to solve the barriers in their work. In turn, the voluntary work brought them benefits in mental and physical health, as well as another chance for growth. Conclusions: Working as volunteers in FSHs not only brought personal benefits to COVID-19 patients but also fulfilled the needs of the healthcare system during public health emergencies.